Studies on the Process Parameters of Rapid Prototyping Technique (Stereolithography) for the Betterment of Part Quality. (10th December 2014) - Gowda, Raju Bangalore Singe; Udayagiri, Chandra Sekhar; Narendra, Drakshayani Doulat
Abstract : Rapid prototyping (RP) has evolved as frontier technology in the recent times, which allows direct transformation of CAD files into functional prototypes where it tremendously reduces the lead time to produce physical prototypes necessary for design verification, fit, and functional analysis by generating the prototypes directly from the CAD data. Part quality in the rapid prototyping process is a function of build parameters such as hatch cure depth, layer thickness, orientation, and hatch spacing. Thus an attempt was made to identify, study, and optimize the process parameters governing the system which are related to part characteristics using Taguchi experimental design techniques quality. The part characteristics can be divided into physical part and mechanical part characteristics. The physical characteristics are surface finish, dimensional accuracy, distortion, layer thickness, hatch cure, and hatch file, whereas mechanical characteristics are flexural strength, ultimate tensile strength, and impact strength. Thus, this paper proposes to characterize the influence of the physical build parameters over the part quality. An L9 orthogonal array was designed with the minimum number of experimental runs with desired parameter settings and also by analysis tools such as ANOVA (analysis of variance). Establishment of experimentally verified correlations between the physical part characteristics and mechanical part characteristics to obtain an optimal process parameter level for betterment of part quality is obtained. The process model obtained by the empirical relation can be used to determine the strength of the prototype for the given set of parameters that shows the dependency of strength, which are essential for designers and RP machine users.